Marcas da docência masculina na educação infantil: experiência, identidade e cotidiano - Oliveira, Adriana Cristina de (2019)
This study addressed male teaching in child education and aimed to analyze the voices and marks of this teaching. These teachers felt they were in an environment where knowledge and affective bonds are built, most often by women since the discourse still states that this profession is predominantly female. Teaching in infant education has been historically and socially constructed as an inherently feminine profession, that is, a maternal function. Thus, we verify a fear for the presence of male figures in the care of young children, even attempts at segregation, since men are considered strangers in school. Therefore, we raised a few hypotheses: the man present in early childhood education feels excluded, out of place, since schools nowadays are mostly occup ied by female teachers. Based on these ideas, this research used a qualitative methodology through open and semi-structured interviews conducted with teachers who work in the public network of municipalities in southern Minas Gerais, Brazil. We considered the following aspects: choice of profession, view of others regarding this choice, fulfillment with the profession, impressions regarding the workplace and teaching colleagues, and prominent experiences during the work as an educator. We based the analyzes on the theoretical contributions of Scott, Louro, Larrosa, and Tomás Tadeu da Silva, focusing on concepts such as gender, experience, and identity. We noticed that many of the perspectives the teachers have of themselves approach the view of many people, that is, still have prejudice. Therefore, they try to avoid certain attitudes for fear of ideas that might be raised by other people in the school community and society.